2002
DOI: 10.1191/1352458502ms851oa
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in multiple sclerosis patients in Spain

Abstract: The Spanish FAMS is a psychometrically valid instrument that allows clinicians and clinical researchers the ability to measure the QOL concerns of MS patients in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 13 publications
4
31
1
1
Order By: Relevance
“…Previous studies from Spain [17] and Italy [41] also reported that EDSS scores were identified as the strong predictors of total FAMS score, and of almost all subscales although subscale scores for family/social well-being were not associated with EDSS score in our study. Large correlation coefficients for mobility and symptoms indicate these aspects are particularly affected by worsening disease severity in our study, and Chang et al also reported that EDSS is a dominant variable in predicting mobility especially by linear multivariate regression analysis [42]. We confirmed that pyramidal dysfunction and visual dysfunction evaluated in EDSS also reduce the FAMS mobility score and that the EQ-5D score is affected by the EDSS score.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies from Spain [17] and Italy [41] also reported that EDSS scores were identified as the strong predictors of total FAMS score, and of almost all subscales although subscale scores for family/social well-being were not associated with EDSS score in our study. Large correlation coefficients for mobility and symptoms indicate these aspects are particularly affected by worsening disease severity in our study, and Chang et al also reported that EDSS is a dominant variable in predicting mobility especially by linear multivariate regression analysis [42]. We confirmed that pyramidal dysfunction and visual dysfunction evaluated in EDSS also reduce the FAMS mobility score and that the EQ-5D score is affected by the EDSS score.…”
Section: Discussionsupporting
confidence: 92%
“…These authors found high values of Cronbach's α coefficients (range: 0.78-0.96), indicating subscale homogeneity comparable with that of the original English version [20].…”
Section: Discussionmentioning
confidence: 77%
“…Graphic presentations may be easier for physicians and patients to grasp [28]. Immediate presentation of results has been discussed as an important and necessary factor for the incorporating HRQL data to be useful and deemed meaningful in routine clinical practice [23][24][25][26][27]. Together with our colleagues at the Center on Outcomes, Research and Education (CORE), we have developed software to administer fixed-form or CAT to patients on tablet-, laptop-, and desktop-computers, over the internet, and using and Interactive Voice Response (IVR), such that a person can complete assessments from any touch tone telephone.…”
Section: Testing Options and Their Implications For Clinical Adoptionmentioning
confidence: 98%
“…One of the primary advantages of electronic data collection is the capability to provide immediate feedback to the patient and/or their health care providers. Studies, including some from our group, on the presentation of patient HRQL information have used either graphic or written displays [12,[22][23][24][25][26][27][28]. Functional scales depict performance in physical, role, emotional, and social areas, and often include questions regarding global quality of life; symptom scales typically assess the more common relevant symptoms such as fatigue, nausea, pain, dyspnea, insomnia, appetite loss, and diarrhea.…”
Section: Testing Options and Their Implications For Clinical Adoptionmentioning
confidence: 99%
See 1 more Smart Citation